Analysis of Covid-19 Impact on Stock’s Abnormal Return in Sub Cigarette Sector Companies Listed on BEI - Mulyaningsih, May; Hartini, Sri; Anggraeni, Resta; Mahendra, Denis Putra (Journal of Social Transformation and Regional Development, 2021)
Covid-19 is an international pandemic that has paralyzed the national economic sector. This study aims to analyze the impact of Covid-19 on stockâ€™s abnormal return in cigarette sub sector companies listed on the Indonesia Stock Exchange in the January-June 2020 period. The population of this study are 5 cigarette sub sector companies listed on the Indonesia Stock Exchange in 2020. The research sample selection uses census method so as to obtain 5 sample companies with an observation period of 5 months (January to May 2020). Secondary data in this study regarding stockâ€™s abnormal returns with actual return and market return proxies. Data obtained from the company’s daily stock price and composite stock price index. Descriptive statistical analysis, data normality test analysis and hypothesis test analysis are processed using SPSS 25. Statistical test with paired sample t test showed no significant difference in abnormal return between the period of 52 days before and when WFH with a significant level of 95% (Î± = 0.05). From the SPSS test results it is known that the significance value obtained is equal to 0.911. When compared with the significance value that has been set. the value is greater (Î±> 0.05). So H1 which states there are differences in stockâ€™s abnormal returns before and during the WFH Covid-19 is rejected.